Comparative Effectiveness and Safety of TURP, HoLEP, and Rezum for Benign Prostatic Hyperplasia: A Systematic Review and Meta-Analysis - Swedan, Qusai Nabeel; A. Alkhatib, Ahmad; Alwraikat, Nadeen Abdelrazzaq; Elsharif, Rail Nazar; Salameh, Mohammad; Badran, Othman; Alsa'di, Seif; Alhamawi, Saed; Shahin, Hamzeh Rushdi (Journal of Neonatal Surgery, 2025)
Background: Benign prostatic hyperplasia (BPH) causes bothersome urinary symptoms in men and often requires surgery. Transurethral resection of the prostate (TURP), holmium laser enucleation of the prostate (HoLEP), and Rezum water vapor therapy are common treatments with different benefits and risks. Methods: This systematic review and meta-analysis included 15 studies (11 randomized controlled trials and 4 cohorts) with over 1500 patients. Using random-effects models, we compared symptom scores (IPSS), urinary flow (Qmax), post-void residual volume (PVR), and safety outcomes such as bleeding, catheter time, and sexual function preservation. Results: HoLEP and TURP both improved IPSS and Qmax significantly, with no difference at most time points. At 12 months, HoLEP showed a small but significant advantage in IPSS (mean difference –0.76; 95% CI –1.25 to –0.27) and greater Qmax (+2–3 mL/s). HoLEP also had lower PVR than TURP (WMD –15.46 mL; 95% CI –20.01 to –10.92). Rezum improved symptoms but less than TURP or HoLEP. Safety favored HoLEP and Rezum, with lower transfusions (RR 0.18; 95% CI 0.07–0.48) and shorter catheterization compared to TURP. Rezum preserved ejaculation better than TURP and HoLEP (p < 0.001). Adverse events and reintervention were low across all treatments. Conclusions: HoLEP and TURP remain effective for BPH, with HoLEP offering modest benefits. Rezum is a minimally invasive option preserving sexual function but with smaller symptom improvement. Treatment should consider patient preferences and clinical context